Efektivitas Layanan Konseling Kelompok dalam Mengatasi Kecemasan Siswa Menjelang Ujian - Yulianti, Yulianti; Ouvia, Nabila; Aprillia, Serly; Chouva, Sabrina Dauna (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Artikel berjudul